2018
DOI: 10.1111/febs.14689
|View full text |Cite
|
Sign up to set email alerts
|

The Golgi ‘casein kinase’ Fam20C is a genuine ‘phosvitin kinase’ and phosphorylates polyserine stretches devoid of the canonical consensus

Abstract: Egg yolk phosvitins, generated through the fragmentation of vitellogenins, are among the most heavily phosphorylated proteins ever described. Despite the early discovery in 1900 that chicken phosvitin is a phosphoprotein and its subsequent employment as an artificial substrate for a number of protein kinases, the identity of the enzyme(s) responsible for its phosphorylation remained a matter of conjecture until present. Here we provide evidence that phosvitin phosphorylation is catalyzed by Fam20C, an atypical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…This indicates that the kinase can phosphorylate rows of consecutive serine residues in MEPE, even though they are not positioned in the consensus sequence. Likewise, FAM20C has been shown to phosphorylate polyserine stretches devoid of Ser‐x‐Glu/pSer motifs in phosvitins ( 25 ) and serine residues in the ASARM of OPN not located in Ser‐x‐Glu motifs. ( 23 ) The 489 Arg‐Asp 508 ‐ myc /His peptide was also observed with two phosphorylations in MEPE expressed without FAM20C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the kinase can phosphorylate rows of consecutive serine residues in MEPE, even though they are not positioned in the consensus sequence. Likewise, FAM20C has been shown to phosphorylate polyserine stretches devoid of Ser‐x‐Glu/pSer motifs in phosvitins ( 25 ) and serine residues in the ASARM of OPN not located in Ser‐x‐Glu motifs. ( 23 ) The 489 Arg‐Asp 508 ‐ myc /His peptide was also observed with two phosphorylations in MEPE expressed without FAM20C.…”
Section: Discussionmentioning
confidence: 99%
“…(22,23) MEPE contains many serine residues having FAM20C recognition motifs, and the C-terminal ASARM motif contains a polyserine stretch that potentially could be targeted by the kinase. (25) Heretofore, no studies have investigated the phosphorylation of MEPE and its ASARM peptide, either in vivo or in vitro. Previous work has used synthetic phosphorylated ASARM peptides to provide important functional information, (7,11,13,17,19,21) ; but no information is yet available on actual phosphorylation sites in MEPE.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we noted a striking similarity between our current study and a previous study from our lab (Yang et al, 2019) that mainly the phosphoproteins were present in the extracellular region of DEW and CEW, respectively. Fam20C is a protein kinase dedicated to the phosphorylation of extracellular proteins (Tagliabracci et al, 2012) and is suggested to be responsible for the phosphorylation of vitellogenins (VTGs) (Cozza et al, 2018). In the current study, we found the VTGs were highly phosphorylated proteins.…”
Section: Motifs Analysis Of Dew Phosphositesmentioning
confidence: 99%
“…Interestingly, one of the earliest recorded instances of phosphorylation and, in retrospect, the existence of protein kinases originated from secreted milk and egg yolk proteins . Following the discovery of phosphorylase kinase , the protein kinase field exploded, culminating in the publication of the “Human Kinome” .…”
Section: Secreted Human Kinasesmentioning
confidence: 99%
“…The flagship member of the Fam20 family of kinases is Fam20C. Fam20C is the physiological GCK and, more recently, has been identified as the phosvitin kinase, an abundant egg yolk protein, which has been known to be highly phosphorylated since the beginning of the 20th century . Fam20C is a secreted protein whose activity can be purified from whey fractions of milk.…”
Section: Secreted Human Kinasesmentioning
confidence: 99%